Harnessing ZnO Nanoparticles for Sustainable River Water Treatment: Efficiency, Mechanisms, and Environmental Implications - Rajat Bhattacharya; Shilpi Shrivastava (The Bioscan, 2025)
It has been revealed after through scientific research that ZnO nanoparticles (ZnO-NPs) are among one of the most if not the most studied nanomaterials brought to use for environmental and specifically wastewater remediation. Its key physicochemical traits are unique and play a key role in the remediation process. These nanoparticles are not only low cost in nature but also possess strong antimicrobial properties with a wide range of direct bandgap from 3.2 to 3.37 Ev and a very high excitation binding energy. When it comes to treatment of river water, the have a dual functionality, they cause photocatalytic degradation of organic pollutants alongside the act of disinfecting the microbial contaminants present in a given sample of river water. This research paper focuses in key areas such as the generation of the reactive oxygen species, chemistry of photocatalysis , mechanism of antimicrobial action of these nanoparticles and their real life applications in the river water matrices. The following are the various parameters of assessment, catalytic stability, leaching behaviour of zinc ion, the matrix effect on the activity, photocatalytic and disinfection performance, the evaluation of its ecotoxicity. However thye entire process also is accompanied by certain identified challenges such as the photocorrosion reducing and the poor utilization of the visible light as it is restricted to specifically the UV region. There are also concerns about the environmental impact. This paper also discusses the strategies for the improvement of the nanoparticles such as elemental doping, catalyst immobilization , formation of heterojunctions and the green synthesis routes which is a more eco-friendly approach. This aims to achieve a promising ZnO NP based solution to wastewater treatment, one which is sustainable and has a high rate of efficacy to bridge the gap between the lab and on field gap.